Fixed prosthetic treatment in patients with cleft lip and palate - Bajevska, Jagoda; Bajevska, Jana; Bajevska Stefanovska, Biljana (Vojnosanitetski pregled, 2017)
Introduction. The prosthetic treatment of patients with cleft palate includes various treatment options such as fixed partial dentures, removable partial prosthesis, etc. The type of prosthetic appliance is determined by the oral health of each individual and the circumstances. We presented three adult patients with the cleft lip and palate subjected to prosthetic treatment. Case report. From the possible prosthetic solutions according to the conditions in the oral cavity and the circumstances, fixed partial dentures veneered with composite or ceramic were chosen. A proper relationship between the teeth was reached with the fixed partial dentures, and function established, the phonetics improved and satisfying aesthetics effect accomplished improving the profile appearance of the patient’s face. Plastic surgery of the nose was performed after that. Conclusion. Multidisclipinary treatment is necessary for favourable long-term outcome in cleft lip and palate patients.
Keywords: cleft lip; cleft palate; prosthodontics; dental prosthesis; denture; partial; fixed; treatment outcome